Populism, twitter, and political communication: an analysis of Jair Bolsonaro's tweets during the 2018 election campaign = Populismo, twitter e comunicação política: análise dos tweets de Jair Bolsonaro durante a campanha eleitoral de 2018 - Mangerotti, Paulo (2021)
The main objective of this paper is to understand populism and its relationship with social media, in particular, to analyze the official Twitter account of the former presidential candidate of Brazil, Jair Bolsonaro. This paper starts with a theoretical review of the definition of populism presented by classic authors such as Boyte and Riessman (1986) and Bell (1992), and by more contemporary authors such as Mudde (2004), Panizza (2005), and Müller (2016). This article also seeks to identify whether the key characteristics of populism were present in the political campaign narratives. Starting from a qualitative and quantitative analysis of content shared on Twitter, we identified populist messages in Bolsonaro's election campaigns, particularly ones that tend to blame the elites and trigger society's fears.